Mechanical and Thermal Properties of Bamboo Fiber–Reinforced PLA Polymer Composites: A Critical Study. (27th December 2022) - Nirmal Kumar, K.; Dinesh Babu, P.; Surakasi, Raviteja; Kumar, P. Manoj; Ashokkumar, P.; Khan, Rashid; Alfozan, Adel; Gebreyohannes, Dawit Tafesse
Abstract : In the past few years, a new passion for the growth of biodegradable polymers based on elements derived from natural sources has been getting much attention. Natural fiber-based polymer matrix composites offer weight loss, reduction in cost and carbon dioxide emission, and recyclability. In addition, natural fiber composites have a minimal impact on the environment in regards to global warming, health, and pollution. Polylactic acid (PLA) is one of the best natural resource polymers available among biodegradable polymers. Natural fiber–reinforced PLA polymer composites have been extensively researched by polymer researchers to compete with conventional polymers. The type of fiber used plays a massive part in fiber and matrix bonds and, thereby, influences the composite's mechanical properties and thermal properties. Among the various natural fibers, low density, high strength bamboo fibers (BF) have attracted attention. PLA and bamboo fiber composites play a vital character in an extensive range of structural and non-structural applications. This review briefly discussed on currently developed PLA-based natural bamboo fiber–reinforced polymer composites concentrating on the property affiliation of fibers. PLA polymer–reinforced natural bamboo fiber used to establish composite materials, various composite fabrication methods, various pretreatment methods on fibers, their effect on mechanical properties, as well as thermal properties and applications on different fields of such composites are discussed in this study. This review also presents a summary of the issues in the fabrication of natural fiber composites.